Development of Protocol for Custom Mixed Fertilizers for Elephant Foot Yam under Intercropping in Coconut Gardens of the Two Agro- Ecological Units of Kerala - Anju, P S; Susan John, K; Bhadraray, Subhendu; Suja, G; Mathew, Jeena; M Nair, K; Sunitha, S; Veena, S S (JOURNAL OF ROOT CROPS, 2017)
Root and tubers are the third most important food crops constituting either the staple or subsidiary food for about one fifth of the world population. Elephant foot yam (EFY) ( Amorphophallus paeoniifolius (Dennst).Nicolson) is a highly potential tropical tuber crop and an ideal intercrop for the coconut gardens of Kerala especially in Agro Ecological Unit (AEU) 9 (South central laterites) and AEU 3 (Onattukara sandy plain) having laterite and sandy soil types. This paper narrates the protocols designed for the development of nutrient mixtures comprising of major, secondary and micronutrients for EFY intercropped in coconut gardens known as ‘custom mixed fertilizers’. It is a mixed multi nutrient carrier whose sources are from inorganic and organic origin which are formulated through specific systematic process of granulation and satisfies the nutritional demands of the crop, specific to agro ecology, soil type and plant need designed taking into account the farmers nutrient management strategy also. The present study for the formulation of the custom fertilizer for the two AEU’s included the optimization of all required nutrients based on the weighted average of the soil data of the two AEU’s comprising of 43 (AEU 3) and 161 (AEU 9) panchayats followed by validation of the optimum fixed through nutrient omission and nutrient level plot techniques for both major, secondary and micronutrients as field experiments in farmers plots and on station. Based on the survey on farmers’ nutrient application strategy, tuber yield, plant nutrient contents, total plant uptake, pre and post soil test data, parameters like nutrient requirement, % contribution from soil, fertilizer use efficiency and nutrients to be applied through fertilizers were arrived. By fitting these parameters in soil test crop response and response curve approaches, the rate/ grades of component nutrients for the custom made fertilizers and their levels of application for the two AEU’s were designed. The three grades designed were tried in two rates in five locations of the two AEU’s with eight treatments (including package of practices and farmers’ practice) replicated thrice in randomized block design.